Peningkatan Manajemen Promosi di Sekolah Swasta Melalui Workshop Integrated Marketing - Indah Purnama Sari; Zaeni Miftah; Heri Nurranto; Ikhsan Maulana; Akbar Ibnu Sopian (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Education helps an individual in developing their personality and social skills. The higher the level of education an individual attains, the better their potential level of well-being. The central role of schools has inspired the team to further examine the conditions of private schools in Bogor Regency, particularly in Bojonggede District. This is because private schools face significant challenges in achieving their New Student Admission (PPDB) targets compared to public schools. Public interest in enrolling their children in private schools is generally low. To address this issue, there is a need to enhance marketing management capabilities integrated with information technology. This article discusses the implementation of an integrated marketing workshop aimed at improving promotional management skills in private schools, with a case study at SMA Muhammadiyah Bojonggede. The workshop was conducted through material presentations, discussions and Q&A sessions, and hands-on practice in the form of simulations. The activity was attended by teachers. The success of the activity was measured by both outcome and process criteria. The results showed an increase in participants' knowledge and skills in integrated marketing strategies.